Antagonistic interactions between garden yeasts and microfungal garden pathogens of leaf-cutting ants - Rodrigues, Andre [UNESP]; Cable, Rachel N.; Mueller, Ulrich G.; Bacci Junior, Mauricio [UNESP]; Pagnocca, Fernando Carlos [UNESP] (Springer, 2009)
We investigate the diversity of yeasts isolated in gardens of the leafcutter ant Atta texana. Repeated sampling of gardens from four nests over a 1-year time period showed that gardens contain a diverse assemblage of yeasts. The yeast community in gardens consisted mostly of yeasts associated with plants or soil, but community composition changed between sampling periods. In order to understand the potential disease-suppressing roles of the garden yeasts, we screened isolates for antagonistic effects against known microfungal garden contaminants. In vitro assays revealed that yeasts inhibited the mycelial growth of two strains of Escovopsis (a specialized attine garden parasite), Syncephalastrum racemosum (a fungus often growing in gardens of leafcutter lab nests), and the insect pathogen Beauveria bassiana. These garden yeasts add to the growing list of disease-suppressing microbes in attine nests that may contribute synergistically, together with actinomycetes and Burkholderia bacteria, to protect the gardens and the ants against diseases. Additionally, we suggest that garden immunity against problem fungi may therefore derive not only from the presence of disease-suppressing Pseudonocardia actinomycetes, but from an enrichment of multiple disease-suppressing microorganisms in the garden matrix.
Keywords: Atta; Symbiosis; Fungus garden; Yeast antagonism